Manajemen Pemanfaatan Dana Desa Dalam Pembangunan Infastruktur Di Desa Puse Kecamatan Dampal Selatan Kabupaten Toli-Toli - Daniel T. Todapa; Juemi Juemi (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
Management of Village Fund Utilization in Infrastructure Development carried out by the Village Government to support community development and empowerment. Qualitative research method with a descriptive approach by examining four aspects, namely planning, organizing, mobilizing and supervising. Data collection techniques include observation, interviews, documentation and triangulation. The determination of informants was carried out "Purposively", namely deliberately selecting 5 people to become informants. The data analysis stages are: Data Collection, Data Condensation, Data Presentation, Conclusion Drawing. The results of this research show that the Management of Utilizing Village Funds in Infrastructure Development in Puse Village, South Dampal District, Toli-Toli Regency begins with the planning process, namely the Village Development Planning Conference (musrenbang). then in the organizing stage at this stage the organizing in terms of division of work is carried out by the village head. Implementation Process where the implementation of activities and supervision processes is carried out by supervisors from the sub-district village and district supervisors.